1989
DOI: 10.1007/bf01540343
|View full text |Cite
|
Sign up to set email alerts
|

Low serum cobalamin levels in a population study of 70- and 75-year-old subjects

Abstract: We examined causes and hematological consequences of low serum cobalamin (vitamin B12) concentration in two representative population samples of 70-year-old (N = 293) and 75-year-old subjects (N = 486). Subjects with values below 130 pmol/liter (4.8% and 5.6%, respectively) were investigated with Schilling test, upper gastrointestinal endoscopy, determination of serum gastrin and group I pepsinogens, and bone marrow examination. Gastrointestinal abnormalities of etiologic significance were found in 26 of the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 32 publications
3
31
0
Order By: Relevance
“…First, undiagnosed clinically significant, severe deficiency of vitamin B12 (serum level <150 pM) is surprisingly prevalent in hospitalized elderly cardiovascular patients in The Netherlands but this prevalence corresponds with present literature data that a clinically significant deficiency of vitamin B12 occurs in 5%-20% of people aged 60 or over in Western populations in general [1][2][3]. However, in our study population, with a mean age of 65 years, we found that nearly half of the patients (45%) were vitamin deficient or had serum levels of vitamin B12 at least lower than 250 pM.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…First, undiagnosed clinically significant, severe deficiency of vitamin B12 (serum level <150 pM) is surprisingly prevalent in hospitalized elderly cardiovascular patients in The Netherlands but this prevalence corresponds with present literature data that a clinically significant deficiency of vitamin B12 occurs in 5%-20% of people aged 60 or over in Western populations in general [1][2][3]. However, in our study population, with a mean age of 65 years, we found that nearly half of the patients (45%) were vitamin deficient or had serum levels of vitamin B12 at least lower than 250 pM.…”
Section: Discussionsupporting
confidence: 84%
“…Vitamin B12 deficiency is prevalent among the elderly [1][2][3][4]. Vitamin B12 is involved in the development of pernicious anemia, neurological disorders, and hyperhomocysteinaemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Early and reliable diagnosis of cobalamin deficiency is important, since potentially irreversible neurological damage may be the first clinical sign. In non-vitamin-supplemented populations, the prevalence of atrophic body gastritis exceeds that of macrocytic anaemia caused by cobalamin deficiency, 2,4 illustrating the slow progress of the atrophy and the long time needed to deplete cobalamin stores. Serum concentrations of total cobalamin have low sensitivity and specificity for diagnosing deficiency, particularly in the large grey zone of values surrounding calculated lower reference limits.…”
Section: Introductionmentioning
confidence: 99%
“…Pernicious anaemia occurs in 0.3% of the total Swedish population and 2% over the age of 70 (Nilsson-Ehle et al, 1989). Neurological signs may be more common in this group Healton et al, 1991).…”
Section: Introductionmentioning
confidence: 99%